Spiritual Leadership as a Model for Islamic Leadership. (2nd January 2017) - Egel, Eleftheria; Fry, Louis W.
Abstract : Western-based models dominate leadership research and practice, although a consensus is emerging that new theories and models are needed to foster cross-cultural understanding and rapprochement. This holds not only for global organizations that employ workers from different cultures but also for public and private organizations whose cultures and employees are grounded in and embrace religious beliefs and practices as central to their work. This article addresses these issues, drawing from spiritual leadership theory and Islamic religious tenets, and performing a theoretical transposition of the components of the spiritual leadership model into a model of Islamic leadership more appropriate for Islamic organizations and organizations employing Muslim workers. Implications for future theory building, research, and practice are discussed.